1995
DOI: 10.1038/376070a0
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles of the receptor tyrosine kinases Tie-1 and Tie-2 in blood vessel formation

Abstract: Tie-1 and Tie-2 define a new class of receptor tyrosine kinases that are specifically expressed in developing vascular endothelial cells. To study the functions of Tie-1 and Tie-2 during vascular endothelial cell growth and differentiation in vivo, targeted mutations of the genes in mice were introduced by homologous recombination. Embryos deficient in Tie-1 failed to establish structural integrity of vascular endothelial cells, resulting in oedema and subsequently localized haemorrhage. However, analyses of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
1,166
2
17

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,653 publications
(1,223 citation statements)
references
References 21 publications
29
1,166
2
17
Order By: Relevance
“…44 Tie2-deficient mice have immature vessels that lack branching networks and periendothelial support cells. 44,45 In our earlier study with sVEGFR-1, -2 and -3, 25 we did not notice such liver toxicity. In the combination group V (sVEGFR-1, -3 and sTie2), a tendency towards a greater amount of ascites was found and 63% of the mice presented edema under the skin.…”
Section: Discussionmentioning
confidence: 62%
“…44 Tie2-deficient mice have immature vessels that lack branching networks and periendothelial support cells. 44,45 In our earlier study with sVEGFR-1, -2 and -3, 25 we did not notice such liver toxicity. In the combination group V (sVEGFR-1, -3 and sTie2), a tendency towards a greater amount of ascites was found and 63% of the mice presented edema under the skin.…”
Section: Discussionmentioning
confidence: 62%
“…Deletion of the rasGAP gene (Henkemeyer et al, 1995) produces a very pleiotropic phenotype as would be expected for a key enzyme which rests downstream of multiple signaling pathways. Vascular defects observed in rasGAP-null embryos (Henkemeyer et al, 1995) resemble the loss of vascular integrity seen in both Tek-and Angiopoietin-1-null embryos (Dumont et al, 1994;Sato et al, 1995;Suri et al, 1996). Furthermore, an abnormal endothelial cell migration pattern was observed in these embryos.…”
Section: Discussionmentioning
confidence: 92%
“…Targeted null mutations in all of these receptors result in embryonic lethality (Shalaby et al, 1995;Fong et al, 1995;Dumont et al, in prep. ;Dumont et al, 1994;Sato et al, 1995;Puri et al, 1995), and the lethal phenotype is distinct for each receptor. These results suggest that the signaling pathways that are mediated by these receptors play unique roles in development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ang2 induces proliferation and migration of endothelial cells and stimulates sprouting of new blood vessels when VEGF is present, whereas it promotes endothelial cell death and vessel regression when the activity of endogenous VEGF is inhibited [46]. Null mutation of the gene for the Tie2 angiopoietin rereceptor gave rise to a phenotype similar to both Ang1 null and Ang2 transgenic mice [47,48]. Since Tie2 is thought to be largely specific to endothelial cells, it has been suggested that Ang1 activates the Tie2 receptor on endothelial cells, resulting in a yet uncharacterized paracrine loop between EC and SMC.…”
Section: Angiopoietins and Tie2mentioning
confidence: 99%